Implementasi Model Pembelajaran Problem Based Instruction (PBI) pada Materi Hukum Newton - Nurhayati Nurhayati; Yoga Budi Bhakti; Dasmo Dasmo (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Problem Based Instruction learning model is very suitable to be applied in physics learning, because it can increase the activeness of learners to engage in the learning process. However, this learning model is still rarely applied by teachers which causes physics learning to become monotonous. The purpose of this study was to apply the Problem Based Instruction learning model to newton's Law mater. This research was conducted by class action research method. Data collection method is done by observation of activities with observation sheets and learning results with test instruments. The results showed that the Problem Based Instruction model can improve the learning outcomes and activities of learners in learning. The application of Problem Based Instruction learning model in physics learning can attract students to learn physics.